As narrativas da liberdade no discurso publicitário dos anos 70 no Brasil: um olhar sociossemiótico sobre a propaganda da calça jeans US Top nas páginas da Revista Geração Pop (1972 - 1975) - Lins, Luizianne de Oliveira (2023)
The present paper aims to investigate the narratives of freedom in the advertising speech directed to youngsters in the 1970’s in Brazil, having as object of study the Magazine Pop Generation (originally Geração Pop). This Brazilian journal exerted a strong influence in a whole generation, presenting varied questionings and being influenced by movements of counterculture, both national and international. We have searched in the study to deepen the comprehension of meanings and conceptions attributed to the idea of freedom in this historical period, characterized by challenging the autocratic order and fighting for autonomy, democratic, sexual and individual freedoms. Concerning to the theorical-methodological aspects, we have adopted in this research the discursive semiotics’ approach. We have based on the theory of text and meaning developed by Greimas and Landowski. The concept of printed media “magazine” was analyzed from ideas of Sodré, whereas the concepts of “generation” and youth were founded in authors like Mannheim, Hobsbawm and Groppo. In relation to documental analysis, we have used the printed editions of the magazine titled Pop Generation, totalizing 32 copies published between the years of 1972 to 1975. The methodology adopted was documental and analytic, focusing on verbal-visual texts analysis present on the magazines in order to understand the way freedom was made figurative in the advertising speech directed to youngsters of the time. As a result, we identified the popularization of jeans pants as an object of value in Brazil and throughout the world, a hundred years after its creation. The first indigo blue denim that manifested being genuinely Brazilian were the jeans pants of the brand US Top. This object of value was launched in 1972, in the same year of the Pop Generation Magazine. These pants, in whose publicity reiterated “to fade and lose the crease”, illustrates the values of freedom proclaimed by an entire generation. This phenomenon took both the jeans pants and the brand US Top to perform a significant role in creation of new meanings about freedom to the youth in Brazilian society. We highlight that the verbal-visual texts found in the magazine manifest daring, provocations and transgressions to the customs of the time. However, in Pop Generation, it was not found any register about the political situation of the country, which lived then a civil-military dictatorship that strongly marked that period